China’s Foreign Direct Investment In South Asia: A Strategic Quest Of China’s Economic Diplomacy - Kafle, Hari Bol (Shanti Journal, 2022)
China has been South Asia’s strategic consort with economic, diplomatic, and developmental influence. China’s support for South Asia has been seen as truly strategic. It has started to overview the countries of its periphery in a more consolidated may rather than focusing on a separate strategy. FDI, especially for South Asia, is a vital source and means of funds, technology transfer, and skill development. To boost up domestic private and public investment, FDI is essential to carry out steady growth of south Asia. In this research paper, China’s FDI in South Asia has been analyzed and examined from the perspective of China’s expansionary integration, key foreign policy objectives, and key achievements. Empirical analysis has been done. Book, journal articles and reports are reviewed. The key global impacts of China’s economic ascendence and achievements of its FDI diplomacy in South Asia are derived in conclusion. Beijing leverages Belt and Road Initiatives in nearly every country having geo-strategic implications, especially at ports through the Indian Ocean. Moreover, China has made significant effort to assuage periphery diplomacy in the region. Going forward, the South Asian countries should be aware of what Beijing is precisely attempting to achieve in the region, with a view of long-term consequences of the novel plan. To reduce the imbalance of FDI tendency, South Asia should reform their policy to maintain steady growth of FDI and to encourage a large size of capital abandoning export of labor force.